2022
DOI: 10.1007/s00425-022-03958-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel aldo–keto reductase gene is involved in 6′-deoxychalcone biosynthesis in dahlia (Dahlia variabilis)

Abstract: Main conclusion:A novel gene belonging to the aldo-keto reductase 13 family is involved in isoliquiritigenin biosynthesis in dahlia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…As with many specialised metabolic pathways (Lou et al, 2022), PKS genes are thought to have arisen from the duplication of a gene from a primary metabolic pathway (fatty acid biosynthesis), followed by neofunctionalisation (Austin & Noel, 2003;Naake et al, 2021) Metabolites synthesised through PKS activity rarely accumulate in planta and are usually processed by diverse tailoring enzymes, of which PKRs are one class, increasing polyketide chemical and functional diversity. Few PKRs have been characterised, notably chalcone reductase (Bomati et al, 2005), but new activities have recently been reported from both bryophytes (T-T. Zhu et al, 2023) and angiosperms (Ohno et al, 2022;L. Zhu et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As with many specialised metabolic pathways (Lou et al, 2022), PKS genes are thought to have arisen from the duplication of a gene from a primary metabolic pathway (fatty acid biosynthesis), followed by neofunctionalisation (Austin & Noel, 2003;Naake et al, 2021) Metabolites synthesised through PKS activity rarely accumulate in planta and are usually processed by diverse tailoring enzymes, of which PKRs are one class, increasing polyketide chemical and functional diversity. Few PKRs have been characterised, notably chalcone reductase (Bomati et al, 2005), but new activities have recently been reported from both bryophytes (T-T. Zhu et al, 2023) and angiosperms (Ohno et al, 2022;L. Zhu et al, 2022).…”
mentioning
confidence: 99%
“…Few PKRs have been characterised, notably chalcone reductase (Bomati et al ., 2005 ), but new activities have recently been reported from both bryophytes (T‐T. Zhu et al ., 2023 ) and angiosperms (Ohno et al ., 2022 ; L. Zhu et al ., 2022 ). PKSs play a crucial role in guiding the metabolic flux during the PKS reaction, stabilising the intermediates formed and preventing them from undergoing nonspecific cyclisation.…”
mentioning
confidence: 99%